Strategic use of social media for small business based on the AIDA model - Hassan, Shahizan; Ahmad Nadzim, Siti Zaleha; Shiratuddin, Norshuhada (Elsevier Ltd, 2015)
This study proposes a strategy for using social media as a marketing tool for small business based on the Attention, Interest, Desire, and Action (AIDA) model. The AIDA model has been applied widely for online marketing strategy but its applicability for social media remains unknown.The focus group discussion was used for data gathering involving twenty two small business entrepreneurs.The finding shows that the model can indeed be applied in strategizing the use of social media for marketing purposes. The proposed strategy serves as a guideline for small business entrepreneurs on how to strategically use social media for marketing.